The child of war in the poem of Qassem Saudi: Case Study diwan "Al-Saud Ala zahre Abi" - Bouadar, Fatima; Khadri, Ali (Journal of Human Sciences, 2022)
The child has a colorful presence in contemporary poetry as one of the main components of the social structure, and poets also paid attention to the subject of the child in their poetry due to their artistic beauty, visual dimensions, and innovative songs. They also portrayed the suffering of children in wars that were affected by their innocence and negatively affected their future lives and well-being.Qassem Saudi is an Iraqi poet who has written poems about the suffering of children in recent decades due to the wars that have taken place in Iraq. He left his literature and realistically paid attention to what happened to the children, including the loss of his family and the destruction of the land and the bloody events of the brutal times. This research, which is based on an analytical-descriptive approach, explains the image of a war-torn child in the poem of Qassem of Saudi Arabia, and the results of the research show that orphanhood and loss, including the loss of the father, caused the child to live in poverty. He had to bear the burden of life alone, which led to his forced labor in the streets for a living. The children also enlisted in the army to defend their homeland, and their destiny was to fight and achieve martyrdom.